Gambaran Kelekatan Remaja dengan Kedua Orang Tua pada Mahasiswa Baru Fakultas Keperawatan Universitas Padjadjaran Tahun Ajaran 2025/2026 - Inka Fadilla Nur Aushaf; Iceu Amira; Kosim Kosim (Universitas Malahayati Lampung, 2026)
ABSTRACT Adolescence is transitional phase that is vulnerable to mental health problems, making emotional support from parents important in helping adolescents cope with developmental demands. Secure attachment with parents serves as a protective factor, particularly for new nursing students as late adolescents who face academic demands and social adaptation during the early period of university life. This study aimed to describe adolescent attachment to fathers and mothers among new students of the Faculty of Nursing at Universitas Padjadjaran in the 2025/2026 academic year. This study used a quantitative descriptive design with purposive sampling involving 160 respondents. Attachment was measured using the Indonesian version of the Inventory of Parent and Peer Attachment IPPA, which includes the dimensions of trust, communication, and alienation. Data analysis was conducted using univariate analysis. Results showed that secure attachment, characterized by high trust, open communication, and low alienation, was slightly more dominant than insecure attachment, which reflects low trust, poor communication, and high alienation. Attachment to fathers showed that 85 respondents (53.1%) were in the secure category and 75 respondents (46.9%) were insecure, while attachment to mothers showed 84 respondents (52.5%) were secure and 76 respondents (47.5%) were insecure. Most students showed secure attachment with both parents, though about half showed insecure attachment. Family-based nursing support is recommended to enhance psychosocial adaptation in early college life. Keywords: Adolescent Attachment, Parents, First-Year Nursing Students, Inventory Of Parent And Peer Attachment (IPPA). ABSTRAK Masa remaja merupakan fase transisi yang rentan terhadap gangguan kesehatan jiwa, sehingga dukungan emosional orang tua menjadi penting dalam membantu remaja menghadapi tuntutan perkembangan. Kelekatan yang aman dengan orang tua berperan sebagai faktor protektif pada mahasiswa baru Fakultas Keperawatan sebagai remaja akhir yang menghadapi tuntutan adaptasi pada awal perkuliahan. Penelitian ini bertujuan mendeskripsikan kelekatan remaja dengan ayah dan ibu pada mahasiswa baru Fakultas Keperawatan Universitas Padjadjaran tahun ajaran 2025/2026. Penelitian ini menggunakan rancangan deskriptif kuantitatif dengan teknik purposive sampling terhadap 160 responden. Kelekatan diukur menggunakan Inventory of Parent and Peer Attachment (IPPA) versi Bahasa Indonesia, mencakup dimensi kepercayaan, komunikasi, dan keterasingan, serta dianalisis secara univariat. Hasil penelitian menunjukkan bahwa kelekatan aman, yang ditandai oleh kepercayaan tinggi, komunikasi terbuka, dan rendahnya keterasingan, sedikit lebih dominan dibandingkan kelekatan tidak aman yang mencerminkan kepercayaan dan komunikasi rendah serta tingginya keterasingan. Kelekatan dengan ayah menunjukkan 85 responden (53,1%) berada pada kategori aman dan 75 responden (46,9%) tidak aman, sedangkan kelekatan dengan ibu menunjukkan 84 responden (52,5%) aman dan 76 responden (47,5%) tidak aman. Sebagian besar mahasiswa baru memiliki kelekatan aman dengan ayah dan ibu, meskipun sekitar setengah responden memiliki kelekatan tidak aman. Dukungan keperawatan berbasis keluarga diperlukan untuk menunjang adaptasi psikososial pada awal perkuliahan. Kata Kunci: Inventory of Parent And Peer Attachment (IPPA), Kelekatan Remaja, Mahasiswa Baru Keperawatan, Orang Tua.